TTIP, ‘Truth’ and the Future of Global Trade - Amy Janzwood (Global justice: Theory, Practice, Rhetoric, 2017)
Review: Ferdi De Ville and Gabriel Siles-Brügge, TTIP: The Truth about the Transatlantic Trade and Investment Partnership (Cambridge; Malden, MA: Polity Press, 2016).